Penerapan metode amsilati dalam pembelajaran kaidah nahwu - dian risky mustofa anwar; Alfi Qurota A’yun; M Agus Mushodiq (Riyahuna: Jurnal Pendidikan Bahasa Arab, 2022)
Grammar is a means for students to be able to read and understand the books they study at the institute, so that students are obliged to study them. Applying optimization of methods in teaching grammar rules and the sciences of the Islamic Institute of Roudlatu Al-Talibin. The type of research used by researchers is field research using a qualitative descriptive approach. The research method used by researchers to obtain information and data related to this research is the use of observation methods, interview methods, documentation methods, and questionnaires. Based on the research conducted, it was found that the application of Amsilati in teaching grammar rules at the Roudlatu Al-Talibin Institute was very effective, and students understood grammar rules more quickly and easily.